The Way of the Fight: An Analysis of MMA Judging - Todd Feldman (Journal of Applied Sports Management, 2020)
Judging is a controversial but rarely studied topic in Mixed Martial Arts (MMA). Most MMA scholarship focuses on health (e.g., head trauma) and training (e.g., dieting, strength, and conditioning), with relatively few exploring matters of judging even though judging is of considerable importance to the appeal and integrity of the sport. Thus, the purpose of this study is to fill this research void by analyzing data on MMA judging decisions to determine if MMA judging follows the criteria approved by the ABC MMA Rules Committee. To evaluate MMA judging, FightMetric data were gathered from a period spanning November 17, 2000 to December 19, 2015. Fight promotions used in the data include the UFC, Strikeforce, and WEC. Logit regressions were used to evaluate the research hypotheses. Several key results stemmed from the analysis, including takedowns landed, knockdowns, significant strikes landed, damage, and control significantly increasingly the likelihood of a fighter winning rounds. However, when a fight is close, judges favor striking as a measure of aggression rather than submission and wrestling attempts. Overall, despite some bias in favor of striking over wrestling and Jiu-Jitsu, MMA judges appear to mostly follow the evaluation criteria provided to them.
Keywords: Governance; Mixed Martial Arts; Policy; Officials; Rules